2015
DOI: 10.1017/s0007485315000474
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Armigeres subalbatus (Diptera: Culicidae) across a temperate altitudinal gradient

Abstract: 11Understanding the impacts of weather fluctuations, and environmental gradients, on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 48 publications
2
39
0
2
Order By: Relevance
“…gambiae distribution with a decrease of mosquito number as altitude increases. Moreover, and given the importance of the spatio-temporal dynamics of vectors in disease transmission (Chaves et al, 2015), there is a crucial need to understand such vector population dynamics in areas with contrasted patterns of transmission (Kamugisha, 2005), to better design tailor-made solutions to control disease transmission.…”
Section: Resultsmentioning
confidence: 99%
“…gambiae distribution with a decrease of mosquito number as altitude increases. Moreover, and given the importance of the spatio-temporal dynamics of vectors in disease transmission (Chaves et al, 2015), there is a crucial need to understand such vector population dynamics in areas with contrasted patterns of transmission (Kamugisha, 2005), to better design tailor-made solutions to control disease transmission.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus and has shown that the organism can also occur in Ar. subalbatus, a species found widely in China, Japan, and Southeast Asia (Chaves et al 2015). The females feed primarily on people and are the natural vectors of filarial worms (Muslim et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All the mosquitoes we collected were female. Environmental conditions can influence insect captures from sweepnetting (Chaves et al 2015), and we guess that the low numbers collected at Pond 4 were partly a result of colder, windier environmental conditions near the Greenland Ice Sheet (Culler et al 2015, Fig. Thus, it is likely that few, if any, males survived long enough to be captured during our sampling.…”
Section: Discussionmentioning
confidence: 99%